Estimulación luminosa intermitente durante el electroencefalograma en epilepsia. Necesidad de homogeneizar su práctica en Hispanoamérica - Montes-Brown, Julio (2024)
Intermittent photic stimulation (IPS) is one of the most common and well-known activation methods used during routine EEG recordings. However, although it is the most straightforwardly standardized activation technique, its methodology still has significant variability, and the interpretation and classification of photoparoxysmal response (PPR) remain largely subjective. Objective: This review aims to provide an updated reference about the standardized methodology to perform the IPS procedure. Additionally, it intends to provide an update on the interpretation and classification of the PPR. A critical analysis about current practical/clinical challenges is formulated, and some potential operational criteria to improve the interrater agreement for the confirmation of PPR are proposed. Conclusions: Proposed operational criteria include, but are not limited to morphology, amplitude, duration, lag, and redundancy. The generalization of using a standardized IPS methodology and defined operational criteria to confirm the presence of PPR can help improve the diagnosis of epilepsy and photosensitivity. Thus, the clinical practice of EEG would maintain its validity, and enhance the care of patients with epilepsy. This review in Spanish can contribute to standardize this clinical practice in Spanish-speaking countries.